Spanish Version of the Flourishing Scale (FS) on the Parents of Children With Cancer: A Validation Through Rasch Analysis - Pozo Muñoz, Carmen; Bretones Nieto, Blanca (Frontiers in Psychology, 2019)
The interest in the study of flourishing is due to the fact that it has been proven that it contributes to a good adjustment to the demands of the environment, relating to indicators of health and wellbeing. There are many researches that have tried to find out what dimensions make it up. The goal of this study is to validate the Spanish Version of The Flourishing Scale (FS), being the first time it is applied to Spanish parents of children with cancer. A total of 138 parents of children with cancer participated in a semi-structured interview. Through IBM SPSS and Winsteps descriptive analyzes and the internal consistency of the FS were calculated. Rasch analysis was used to study the dimensionality of the scale, the adjustment of each one of the items, the reliability values for the items and for the people, the validity of the construct, the functioning of the response categories and the differential item functioning (DIF). The external construct validity of the FS was examined with associated measures. Results found that parents indicated a flourishing attitude (M= 3,85; sd= ,63). We confirm that the FS maintains an adequate internal consistency and a unidimensional structure. We observed a good alignment between the question and the person’s abilities as soon as a high reliability for the items. Although the sample is large enough to corroborate the difficulty hierarchy of the items, the construct validity could be improved by introducing items of moderate and high difficulty. On the other hand, the answer category 3 overlaps with the 2 and 4, so we propose possible solutions. Regarding a possible DIF, this exists in relation to “gender”, “level of education” and “by the situation with respect to treatment”. Finally, the convergent validity of the FS is demonstrated, there being a significant correlation with wellbeing, satisfaction with social support and coping. In general, the results show adequate psychometric properties of the Spanish version of the FS, so we recommend integrating it in psychosocial interventions aimed at parents of children with cancer, in order to provide them with resources to deal with the disease.